2000
DOI: 10.1126/science.287.5453.637
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Breaking Mechanism of Multiwalled Carbon Nanotubes Under Tensile Load

Abstract: The tensile strengths of individual multiwalled carbon nanotubes (MWCNTs) were measured with a "nanostressing stage" located within a scanning electron microscope. The tensile-loading experiment was prepared and observed entirely within the microscope and was recorded on video. The MWCNTs broke in the outermost layer ("sword-in-sheath" failure), and the tensile strength of this layer ranged from 11 to 63 gigapascals for the set of 19 MWCNTs that were loaded. Analysis of the stress-strain curves for individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

75
2,224
9
44

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 4,774 publications
(2,469 citation statements)
references
References 25 publications
75
2,224
9
44
Order By: Relevance
“…Treacy et al [12] estimated the Young's moduli of 11 different isolated MWCNTs to be between 0.40 to 4.15 TPa, with an average value of 1.8 TPa. On the other hand, Yu et al [13] found that the tensile strength of MWCNTs can be as high as 63 GPa. Furthermore, the electrical properties of CNTs respond to applied mechanical stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Treacy et al [12] estimated the Young's moduli of 11 different isolated MWCNTs to be between 0.40 to 4.15 TPa, with an average value of 1.8 TPa. On the other hand, Yu et al [13] found that the tensile strength of MWCNTs can be as high as 63 GPa. Furthermore, the electrical properties of CNTs respond to applied mechanical stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and experimental work on the mechanical properties of individual or bundles of CNTs proceeded well at the end of the last century. [1][2][3] It is now widely held that the modulus and strength of a typical single-walled carbon nanotube (SWNT) can reach 640 and 37 GPa, respectively, which surpass those of all existing materials. [4] However, because of weak intertube interactions, it is still a great challenge to acquire such super mechanical properties when CNTs are assembled as macroarchitectures (such as fibers and films).…”
mentioning
confidence: 99%
“…Experimental [3][4][5] and theoretical works [6,7] indicate that the axial stiffness and strength of CNTs are of the order of 1 TPa and 50 GPa, respectively, both in agreement with those for in-plane graphite [8] and graphene [9]. The interaction between walls in CNTs and the self-interaction of CNTs in bundles, mostly governed by van der Waals forces, is also similar to the interaction between graphene layers in graphite and results in a low shear strength between adjacent graphene layers that facilitates CNTs sliding [10].…”
Section: Introductionmentioning
confidence: 99%